The Representation of Islamic Values in the Cultural Collections of Lampung Museum as a Medium of Cultural Da'wah - Dinda Nurul Fadillah; M. Mawardi J; Nadya Amalia Nasoetion (Fakultas Ushuluddin Adab dan Dakwah UIN Sultanah Nahrasiyah Lhokseumawe, 2026)
The existence of museums in the context of Indonesian Muslim society holds untapped potential as a place for da'wah communication. This study addresses the gap between the rich Islamic-themed collection at Lampung Ruwa Jurai Museum and the limited academic attention to its cultural da'wah dimension. This study aims to examine the representation of Islamic values in the Lampung Museum's cultural collection and its position as a medium of cultural da'wah. Using a descriptive qualitative approach and Stuart Hall's representation theory, data were collected through observation, interviews with six purposively selected informants (one curator, one customary leader, four visitors), and collection documentation. Analysis used the interactive model of Miles, Huberman, and Saldana. The findings show that the value of faith is represented through calligraphic carvings on trays, moral values through changes in traditional Lampung bridal attire that cover more of the aurat following acculturation with Islam, and worship values through the egg-flower tradition, which embodies gratitude, prayer, and almsgiving. Most visitor informants demonstrated a dominant reading, while one showed a negotiated reading. These findings are limited to the analysis of three main collections and six informants and cannot be generalized to the entire museum collection. The findings indicate that Lampung Museum has the potential to serve as a space for representing Islamic values and a medium of cultural da'wah by conveying symbolic messages to the public.